Testicular Cancer: Genes, Environment, Hormones - De Toni, Luca; Šabovic, Iva; Cosci, Ilaria; Ghezzi, Marco; Foresta, Carlo; Garolla, Andrea (Frontiers in Endocrinology, 2019)
Testicular cancer represents one of the most peculiar clinical challenge at present. In fact, if on a side current treatments are so effective to ensure a five-years disease-free survival rate in nearly 95% of patients. On the other side, testicular cancer represents the most frequent newly diagnosed cancer in men between the ages of 14 and 44 years, with an incidence ranging from <1 to 9.9 affected individuals per 100,000 males across countries, and the overall incidence increasing worldwide. Furthermore, cancer survivors show a 2% risk of developing cancer in the contralateral testis within 15 years of initial diagnosis. This complex and multifaceted scenario requires great deals of efforts to understand the clinical base of available evidence. It is now clear that genetic, environmental and hormonal risk factors concur and mutually influence both the development of the disease and the prognosis, in terms of response to treatment and risk of recurrence. In this paper, the most recent issues describing the relative contribution of the aforementioned risk factors in testicular cancer development are discussed. In addition, particular attention is paid to the exposure to environmental chemical substances and thermal stress, whose role in cancer development and progression has been recently investigated at molecular level.